Analisis Pengaruh Zakat, Infaq Dan Sadaqah Terhadap Pertumbuhan Ekonomi Dengan Indeks Pembangunan Manusia Di Indonesia Sebagai Variabel Intervening - Putri Mardiyyah Hasibuan; Nur Ahmadi Bi Rahmani; Budi Dharma (Student Research Journal, 2023)
This research aims to determine Zakat, Infaq and Sadaqah on economic growth with the Human Development Index in Indonesia as an intervening variable. The method used in this research is quantitative, data collection is carried out by accessing reports that have been published by the Central Statistics Agency and the National Zakat Amil Agency. The data that has been obtained is then processed using Eviews 10 version. Based on the results of simultaneous regression coefficient test calculations (f test), it can be concluded that the variables Zakat (X1), Infaq and Sadaqah (X2) and the Human Development Index (Z) have a positive effect on economic growth (Y), namely the coefficient value is 60.34371 with a probability value of 0.00000 < 0. And the coefficient of determination test (R2) is 0.554560, this shows that the variables Zakat, Infaq and Sadaqah have an influence on economic growth by 55.45% while the remaining 44.55% is influenced by other variables which are not included and not researched. in this research.